Nutritional efficiency of rubber rootstocks - Vieira, Noemi Cristina de Souza [UNESP]; Junior, Enes Furlani [UNESP]; Nocchi, Raiana Crepaldi de Faria; Paixão, Amanda Pereira [UNESP]; Pereira, Magno; Junior, Erivaldo José Scaloppi; Silva, Dayane Bortoloto da [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2022)
The study of the nutritional efficiency of seedlings of rubber tree rootstocks is an important tool to select genotypes responsive to fertilization, thus ensuring the rationalization of the use of fertilizers. In this context, the objective of this study was to evaluate the efficiency of absorption, transport and use of nutrients in rootstocks from seeds of clones GT1, PB235 and IAN873 cultivated in a suspended nursery in the municipality of Ilha Solteira-SP. The experiment was carried out in an open-air nursery installed at the Faculty of Engineering - UNESP, Ilha Solteira- SP campus, during the period from March/2018 to January/2019. The experimental design used was randomized blocks, in a 3 x 5 factorial scheme, with three rootstocks GT1, PB235 and IAN873 and five times of data collection 60, 120, 180, 240 and 300 days after transplanting (DAT), with three replications of 10 seedlings per plot. The rootstocks showed similarity in terms of absorption efficiency (EA) and transport efficiency (ET) for macronutrients, and transport efficiency (ET) of micronutrients, however, they differed in terms of nutrient utilization efficiency (EU). IAN873 showed higher performance in EU of P, K and Fe, in contrast, rootstock GT1 had lower EU of Ca, Mg, Mn, Zn and Cu. Although the EA of Zn was superior to Cu, the rootstocks showed better EU of Cu in relation to Zn.
Eficiência nutricional de porta-enxertos de seringueira
Keywords: Absorption efficiency (EA); Hevea brasiliensis (Willd. Ex Adr. de Juss.) Muell.-Arg; Suspended bench seedling production; Transport efficiency (ET); Utilization efficiency (EU)